A framework for good health governance during the Covid-19 pandemic response and recovery in South Africa - Bakam, Genevieve; Edoun, E.I.; Pradhan, Anup; Sukdeo, Nita (Technium Social Sciences Journal, 2022)
From the Ubuntu philosophy to peace management, good governance application enables socioeconomic and environmental development. It happens that a fear atmosphere due to global disaster in health care management compromise good governance sustainability. This study seeks to design a framework for good health governance during the Corona Virus Disease 2019 (COVID-19) pandemic response and recovery in South Africa. Using a case study, research data were collected through questionnaire and analysed using correlation, variance and regression tools in statistical package for the social sciences (SPSS). 75%, 74%, 69% and 82% of respondents agreed and strongly agreed that good health governance metrics, government modernisation, pandemic governance strategies and pandemic governance challenges constitute the components of an effective framework for good health governance during the response and the recovery phase of the COVID-19 pandemic. Additionally, there was a positive, strong and significant connection between the framework for good health governance and its constituents. Although health measures were taken at the early stage to limit the severe consequences of the pandemic in South Africa, the government is still required to redouble efforts in implementing rules of laws, initiate and develop capacity building, build integrity cultures together with the implementation of e-governance to ensure effective responsiveness and recovery. Countries in respective regions around the world should join forces to combat the spread of the virus through adoption of international good health governance solutions as proposed by the World Health Organisations. In South Africa specifically, government should incessantly initialise post-pandemic resolutions beforehand to counterattack continuous shocks on the country’ economic growth.